Research groups in Social Anthropology in Spain: an overview - Sanz Abad, Jesús (Revista de Antropología Social, 2011)
In this introduction and presentation of this monography, a review is done on the evolution of Social Anthropology in Spain, as well as the evolution of the topics that have prevailed under the discipline. Insofar as there is an analysis of the groups represented or not in this volume, there is an overview on the current status of Anthropological research Spain. In the second part of the text, the reader will find a brief comment on the theoretical and methodological characteristics collected in the texts. In light of the texts there is a reflection on the relevant changes and developments that have taken place in the discipline. It also highlights the central role of ethnography as the main hallmark of Anthropology in the new context of globalization analysis.
Keywords: Social Anthropology; research groups in Spain; state of the art; ethnography; research topics